Ultrasonography (USG) Accuracy in Diagnosing Breast Cancer; a Cross-sectional Study at Prima Medika General Hospital Denpasar - Putu Dewi Ari Wulandari; I Bagus Gede Dharmawan (Jurnal Epidemiologi Kesehatan Komunitas, 2023)
Background: Ultrasonography (USG) radiological examination can be an early detection of breast tumors before they develop into malignancy. The aim of our study was to determine the accuracy of USG examination in diagnosing breast cancer at Prima Medika Hospital.Methods: We conducted a cross-sectional study from January to December 2021 at Prima Medika Hospital Denpasar in patients who had symptoms of breast cancer had breast USG examinations and biopsy examinations of 51 samples. We collected data by tracing medical records and in descriptive analysis and cross-tabulation analysis to determine the sensitivity, specificity, positive predictive values and negative predictive values.Results: 72.5% of 51 patients were over 36 years old, 47.1% symptoms of a lump in their left breast. USG examination in detecting breast cancer has a sensitivity of 90.9%, a specificity of 93.1% then a positive predictive value of 92.9% and a negative predictive value of 90.1%.Conclusion: USG examination has a high accuracy in diagnosing breast cancer. Radiology specialists are expected to use USG examination as an early detection tool before conducting a histopathological gold standard examination.